Library Drone Delivery Programme: A Study - Nath, Francis (DESIDOC Journal of Library & Information Technology, 2018)
There has been a significant paradigm shift in drone applications. Exclusively available only for military missions in the past application of drones has made its way to various platforms and the library is the one such platform that is being examined here. A significant feature of a drone that is its delivery feature can prove immense potential in bringing information to the users in the form of books or other library documents. A study is done on various elements of the drone facility, its payload capacity, the integration of such a facility with the library, the procedure of processing user requests via drone delivery, drone technology and procedure for making delivery, the regulations in India concerning flying of drones and the advantages and limitations of using drone delivery service. It is an emerging technology that has yet to see its full potential in civilian platform. In today’s digital era with diminishing demand for physical books caused by electronic documents, drone delivery can breathe fresh air into the library services by bringing back the popularity of books and making them available to the users in the click of a button.